What is quality in art? a meditation based on European paintings from the 15th to the 18th centuries - Vergara, Alexander 1960- (Hannibal, 2024)
"Throughout history, human beings have excelled at creating art of the highest quality. Aristotle wrote that Homer surpassed all others and Pliny the Elder referred to masterpieces that we never tire of admiring . Velázquez distinguished between portraits made with art and those that were not. What did they all mean exactly? What do we mean when we say that a work of art is good, of high quality? This book is an attempt to explain this central question, which remains surprisingly unexplored.Alejandro Vergara argues that a deep knowledge of the history of art provides us with the tools to approach this issue objectively . He then invites the reader to share with him a Socratic voyage of discovery, gradually unveiling arguments that can assist us in understanding this elusive and crucial concept."
Keywords: Geschichte 1400-1800; Ästhetik; Malerei; Kunst; Europa